2021
DOI: 10.1177/25161032211034255
|View full text |Cite
|
Sign up to set email alerts
|

Mental health services and psychotropic medications provided to children at risk for placement instability in foster care

Abstract: Children at risk for placement instability are subpopulation in out-of-home care with a critical need for enhanced mental health services, but little is known about the types and adequacy of the mental services they receive. This descriptive study sought to identify the types of mental health services and psychotropic medications provided to children with a risk for moves, foster parents’ perceptions of their adequacy, consistency of therapy services with evidence-based models, and racial and gender difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Another notable finding was the high rate of prescription of psychotropic medications among the FC sample, with 98.9% of these subjects taking one or more of these medications; this is consistent with findings from other studies on out-of-home care [ 49 , 54 ]. These findings indicate that psychotropic medication may be prescribed at particularly elevated rates to youth in FC with a history of hospitalisation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Another notable finding was the high rate of prescription of psychotropic medications among the FC sample, with 98.9% of these subjects taking one or more of these medications; this is consistent with findings from other studies on out-of-home care [ 49 , 54 ]. These findings indicate that psychotropic medication may be prescribed at particularly elevated rates to youth in FC with a history of hospitalisation.…”
Section: Discussionsupporting
confidence: 88%
“…Given the recognition of existing deficits in mental health services and the barriers to receiving community-based treatment, the increased use of acute health services is of particular concern as it suggests that the existing mental health service model is not appropriate and that the needs of this specific population are not being fully met. Addressing these disparities in service use is an important step toward building a more evidence-based and specialist community-based mental health system, as generic services do not do justice to the complexity of these children [ 49 ]. Additionally, improving the adequacy and quality of care of current services, both in the inpatient unit and in the emergency department, should be a priority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These may constitute a safer and underutilized opportunity for reducing the risk of PRTF admission. Although many youth with externalizing disorders receive some form of psychotherapy, a recent study indicated that psychotherapy models typically used were not evidence-based, nor did these services tend to include caregiver training (Leathers et al, 2021). For youth in foster care, several practices and programs for treating aggressive behavior have been found to be effective, including multisystemic therapy, cognitive behavioral therapy, dialectical behavior therapy, and parental management training (e.g., Triple P; Ghosh et al, 2017; Miller et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical guidelines call for the treatment of DBDs with APs adjunctively only after psychosocial and non-AP psychotropic medications have been applied (American Academy of Child and Adolescent Psychiatry [AACAP], 2009[AACAP], , 2011. Although several psychosocial interventions, including Triple-P and cognitive behavioral therapy have been shown to be effective at treating forms of DBD, the clinical guidelines calling for these therapies prior to prescribing are not universally followed (Aitken et al, 2018;Daviss et al, 2016;Ghosh et al, 2017;Leathers et al, 2021;Patel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%